PHOTOMETRIC OBSERVATIONS OF THE R AQUARII SYSTEM - Khudyakova, T. N. (Одеські астрономічні публікації, 2017)
Photometric BVRIJHK observations of the symbiotic star R Aqr are presented. The data were obtained at Byurakan Station of the St.Petersburg University Astronomical Observatory during the interval 1971- 1991, using AFM-6 photometer (C-8 type photocatode) at the 48 cm telescope (BV), the IKAF-1 photometer (SI type photocatode) at the 48 cm and 62 cm telescopes (HI), IKAF-2 PIS photometer at the 62 cm telescope (JHK). The photometry was made and reduced to Johnson system in the usual manner for broad-band photometry. The main part of the data were obtained in red and near infrared, and my report will concern the cold component.